2015
DOI: 10.1016/j.sleep.2015.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Restless legs syndrome does not affect 3-year mortality in hemodialysis patients

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. Original Highlights of the studyWe evaluated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
28
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 50 publications
2
28
1
Order By: Relevance
“…Some studies also found that RLS/WED is associated with enhanced mortality in ESRD patients [6,8,11,22,25], particularly those with severe forms of RLS/WED [8,11]. By contrast, Stefanidis et al [26] recently reported that RSL/WED did not influence the 3-year mortality rate in a large cohort of ESRD patients, sparking a debate on the impact of RSL/WED on mortality in patients on haemodialysis (HD) [27,28]. …”
Section: Introductionmentioning
confidence: 99%
“…Some studies also found that RLS/WED is associated with enhanced mortality in ESRD patients [6,8,11,22,25], particularly those with severe forms of RLS/WED [8,11]. By contrast, Stefanidis et al [26] recently reported that RSL/WED did not influence the 3-year mortality rate in a large cohort of ESRD patients, sparking a debate on the impact of RSL/WED on mortality in patients on haemodialysis (HD) [27,28]. …”
Section: Introductionmentioning
confidence: 99%
“…In addition, the study by Baiardi et al [7] revealed no difference among the causes of death between the 2 groups; this is in contrast to previous studies linking RLS to cardiovascular diseases [5] . The studies by Stefanidis et al [6] and Baiardi et al [7] clearly suggest that mortality in HD patients is not influenced by the presence of RLS/WED, as they provide no clinical evidence linking uremic RLS/ WED to cardiovascular mortality.Considering the discordant literature on the mortality risk in uremic RLS patients and the fact that cardiovascular disease is the number one cause of death in HD patients, the recent evidence by Baiardi et al [7] provides important data that will inform the design of the next prospective Disorders of the brain are becoming more prevalent and are both threatening quality of life as well as creating major challenges for the national health systems. Restless legs syndrome (RLS; or Willis/Ekbom disease) is one of the most common neurological disorders associated with significant personal, social and economic burden.…”
mentioning
confidence: 96%
“…
there was no significant association between RLS and 3-year mortality, either with age and gender as covariates [6] .In the current issue of the American Journal of Nephrology , an unprecedented 15-year follow-up of RLS survivorship is presented by Baiardi et al [7] . These investigators demonstrate that RLS-HD patients had a lower mortality rate compared to those HD patients without the syndrome (63.8% [4.3%/year] RLS-HD vs. 87.6% [5.8%/year] non-RLS HD, p = 0.04).
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…116 However, a recent study could not confirm an increased mortality in ESRD patients with RLS at 3-year follow-up (N=549). 117 Thus, the association between mortality and RLS/PLMS is not definitive at this time, reinforcing the need for further studies.…”
mentioning
confidence: 99%